2006
DOI: 10.1007/s11458-006-0045-6
|View full text |Cite
|
Sign up to set email alerts
|

Studies on photocatalytic activity of Ag/TiO2 films

Abstract: Ag/TiO 2 photocatalytic films were produced by hybrid sol-gel method. The photocatalytic degradation of methyl orange (MO) in aqueous solution under 365 nm irradiation on TiO 2 and Ag/TiO 2 thin films was investigated. The state and amount of Ag species within the film and the enhancement mechanism of photocatalytic activity of Ag/TiO 2 were discussed. With a loading molar ratio of Ag/Ti = 0.135 in TiO 2 film, the maximum catalytic efficiency was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The use of TiO 2 in suspension form is efficient due to its large surface area but there are four major technical challenges that restrict its large-scale application and its use in water-treatment technologies. Firstly, it has a relatively wide band gap (∼3.2 eV, which falls in the UV range of the solar spectrum), and therefore it is unable to harness visible light thus ruling out sunlight as the energy source of its photoactivation [9,16,211,[226][227][228][229]. Secondly, it has low quantum efficiency due to the low rate of electron transfer to oxygen resulting in a high recombination of the photogenerated electron-hole pairs [226,227,230].…”
Section: Environmental Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of TiO 2 in suspension form is efficient due to its large surface area but there are four major technical challenges that restrict its large-scale application and its use in water-treatment technologies. Firstly, it has a relatively wide band gap (∼3.2 eV, which falls in the UV range of the solar spectrum), and therefore it is unable to harness visible light thus ruling out sunlight as the energy source of its photoactivation [9,16,211,[226][227][228][229]. Secondly, it has low quantum efficiency due to the low rate of electron transfer to oxygen resulting in a high recombination of the photogenerated electron-hole pairs [226,227,230].…”
Section: Environmental Applicationsmentioning
confidence: 99%
“…Firstly, it has a relatively wide band gap (∼3.2 eV, which falls in the UV range of the solar spectrum), and therefore it is unable to harness visible light thus ruling out sunlight as the energy source of its photoactivation [9,16,211,[226][227][228][229]. Secondly, it has low quantum efficiency due to the low rate of electron transfer to oxygen resulting in a high recombination of the photogenerated electron-hole pairs [226,227,230]. Thirdly, when used in a suspension, titanium dioxide aggregates rapidly due to its small size (4 nm to 30 nm) and its aggregates may cause scattering of the light beam resulting in loss of catalytic efficiency [66,211,231].…”
Section: Environmental Applicationsmentioning
confidence: 99%
“…Although the use of TiO 2 in suspension form is more feasible due to its large surface area, there are four major technical challenges that restrict large-scale application of titania. Firstly, it has a relatively wide band gap (∼3.2 eV, which falls in the UV range of the solar spectrum); therefore, it has minimal absorption of visible light and is unable to harness visible light hence ruling out sunlight as the energy source of photoactivation [7,8,[10][11][12][13][14]. Secondly, it has low quantum efficiency due to the low rate of electron transfer to oxygen resulting in a high recombination of the photo generated electron-hole pairs [5,7,10].…”
Section: Introductionmentioning
confidence: 99%
“…Ag and Co were used for comparative purposes. Metal-ion-doped TiO 2 (m-TiO 2 ) thin films have been previously synthesised using either sol-gel, liquid-phase deposition or colloidal sol techniques [5,7,10,19,28] but not using the layer-by-layer self-assembly deposition. To the best of our knowledge, the application of the LbL technique and the polyelectrolyte system used to immobilise the catalysts as described in this study has not been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the 2p-Ti peaks are observed at 462. 21 [19,20]. The binding energy observed for the 3d 5/2 in AgTi was observed at 365.25 eV, which is lower than the analog normal modes reported for metallic silver or silver oxides.…”
Section: Resultsmentioning
confidence: 67%